PENGARUH ETIKA DAN SELF EFFICACY TERHADAPA PRESTASI BELAJAR MAHASISWA (STUDI PADA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TANJUNGPURA PONTIANAK) - -, DAHLAN B B1021141004 (Jurnal Manajemen Update, 2018)
ABSTRACKLearning achievement is a benchmark of students' ability after learning activities for a certain period of time. The learning achievements of the students of the Faculty of Economics and Business at Tanjungpura University are generally varies, there are students who scored high and low as well. Therefore, it is necessary to further study the factors that influence student achievement. Learning achievement is a benchmark of students' ability after learning activities for a certain period of time. The learning achievements of the students of the Faculty of Economics and Business at Tanjungpura University generally differ from those that are high and low. Therefore, it is necessary to further study the factors that influence student achievement. This research aims to test and analyze the influence of ethics and self efficacy towards achievement students of Faculty of Economics and Business at Tanjungpura University. The sample in this study is 100 respondents. The sampling technique used is quota sampling. This study used multiple linear regression data analysis techniques using SPSS version 21.0. The results showed that ethics and self efficacy had a positive and significant effect on the achievement of students at Faculty of Economics and Business, Universitas Tanjungpura with determination coefficient (adjusted R2) of 49 %, while the remaining 51% was influenced by other variables which are not examined in this study.Keywords: Ethics, Self Efficacy, Student Learning AchievenmentDAFTAR PUSTAKAAgoes & Ardana. (2011). Etika Bisnis dan Profesi. Jakarta: Salemba EmpatArijanto, A. (2012). Etika Bisnis bagi Pelaku Bisnis. Jakarta: PT Rajagrafindo PersadaBandura, A. (1997). Self Efficacy The Exercise of Control. New York: W.H. Freeman & Company.Bandura, A. (1999). Self Efficacy in Changing Societes. New York: Cambridge University Press.Ghozali, I. (2013). Aplikasi Analisis Multivariate dengan Program IBM SPPS 21. Semarang: Badan Penerbit Universitas DiponegoroGkorezis, Kostagiolas & Niakas. (2017). Linking Exploration to Academic Performance: The Role of Information Seeking and Academic Self Efficacy